CAD–CAM plates versus conventional fixation plates for primary mandibular reconstruction: A biomechanical in vitro analysis. Issue 11 (November 2017) - Rendenbach, Carsten; Sellenschloh, Kay; Gerbig, Lucca; Morlock, Michael M.; Beck-Broichsitter, Benedicta; Smeets, Ralf; Heiland, Max; Huber, Gerd; Hanken, Henning
Abstract: Background: CAD/CAM reconstruction plates have become a viable option for mandible reconstruction. The aim of this study was to determine whether CAD/CAM plates provide higher fatigue strength compared with conventional fixation systems. Material and methods: 1.0 mm miniplates, 2.0 mm conventional locking plates (DePuy Synthes, Umkirch, Germany), and 2.0 mm CAD/CAM plates (Materialise, Leuven, Belgium/DePuy Synthes) were used to reconstruct a polyurethane mandible model (Synbone, Malans, CH) with cortical and cancellous bone equivalents. Mastication was simulated via cyclic dynamic testing using a universal testing machine (MTS, Bionix, Eden Prairie, MN, USA) until material failure reached a rate of 1 Hz with increasing loads on the left side. Results: No significant difference was found between the groups until a load of 300 N. At higher loads, vertical displacement differed increasingly, with a poorer performance of miniplates ( p  = 0.04). Plate breakage occurred in miniplates and conventional locking plates. Screw breakage was recorded as the primary failure mechanism in CAD/CAM plates. Stiffness was significantly higher with the CAD/CAM plates ( p  = 0.04). Conclusion: CAD/CAM plates and reconstruction plates provide higher fatigue strength than miniplates, and stiffness is highest in CAD/CAM systems. All tested fixation methods seem sufficiently stable for mandible reconstruction.